Pengaruh Ukuran Wadah Kemasan Mika Terhadap Kualitas dan Umur Simpan Buah Stroberi (Fragaria sp.) - YONATHAN CHRISTIAN SIMATUPANG; MADE SUDIANA MAHENDRA; ANAK AGUNG GEDE SUGIARTA (Agrotrop : Journal on Agriculture Science, 2021)
Influence of Mica Packaging Container Sizes on Quality and ShelfLife of Strawberry (Fragaria sp.). This study aimed to determine the effect of plastic mica container size with a total of 15 pieces of packaging and determined the best treatment for the shelf life of strawberries (Fragaria sp). This study useds a complete randomized design methodology (CRD) with one treatment, namely the type of plastic mica container size with various types of packaging types as follows: type 1 (K1), type 2 (K2), type 3 (K3) and number 15 fruit packs. The observed variables were weight loss, hardness level, shelf life, organoleptic test, respiration rate and vitamin C. The size of the packaging containers affected the physico-chemical changes in the strawberries. The treatment influenced the physico-chemical changes in the strawberries, such as the rate of respiration and vitamin C levels. The best packaging size was the smallest size (K1 ) K2 and K3 packaging container sizes. This is indicated by the lowest weight loss variable, with the value of 0.20%, the lowest value of respiration rate (20.61 CO2/ kg/hour), the highest vitamin C content (72.89 mg/100g), while in the organoleptic test, the smallest container size resulted in the highest score in fruit colour, container size has a score highest in the observation of fruit color, fruit appearance and fruit aroma. Observation of the shelf life of strawberries showed that the container size of K1 (the smallest) had an average shelf life better than K2 and K3. K1 container size produced a shelf life average of 4 days while K2 container size produce a shelf life average of 3,4 days. The shortest shelf life average was recorded in the K3 container size with a value of 3,2 days. It is concluded that the shelf life of strawberries in a packaging container at a temperature of 28-30ºC can be as long as 4 days.